EFFECT OF FEEDING GUAVA (PSIDIUM GUAJAVA LINN) LEAF MEAL ON GROWTH PERFORMANCE, SURVIVAL AND DIGESTIBILITY OF LABEO ROHITA (HAMILTON, 1822) FINGERLINGS - KUMAR, PAWAN; OJHA, M. L.; SHARMA, B. K.; YADAV, NITESH KUMAR; SINGH, HARI (Journal of the Inland Fisheries Society of India, 2026)
The present study was conducted to evaluate the effect of dietary protein supplement, Guava (Psidium guajava Linn) leaf meal on the growth, survival rate and digestibility in Labeo rohita fingerlings. The study was conducted for a period of 60 days. The five levels of dietary supplementation of guava leaf meal was incorporated in basal feed 0 % (T1), 0.05% (T2), 0.1 % (T3), 0.15 % (T4), and 0.2 % (T5) by replacing equal amount of basal diet. Fishes were fed at the rate of 3 per cent of their body weight in split does in the form of pellets. Feeding was done 2 times in a day. The growth performance in terms of weight gain (g) (82.293±0.8 e), % weight gain (167.040±1.908e), net gain in length (8.950±0.015cm) specific growth rate (1.161±0.002 %c) and gross conversion efficiency (GCE) (0.592±0.005 d) was observed significantly (P